2020
DOI: 10.1016/j.ins.2019.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Identification of influencers in complex networks by local information dimensionality

Abstract: The identification of influential spreaders in complex networks is a popular topic in studies of network characteristics. Many centrality measures have been proposed to address this problem, but most have limitations. In this paper, a method for identifying influencers in complex networks via the local information dimensionality is proposed. The proposed method considers the local structural properties around the central node; therefore, the scale of locality only increases to half of the maximum value of the … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
48
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(48 citation statements)
references
References 46 publications
0
48
0
Order By: Relevance
“…Researchers have analysed network properties from different perspectives, depending on the type and complexity of networks. Entropy-based analysis has been used to identify influential nodes using local information dimensionality [37]. Fractal dimensions are being explored to determine the vulnerability of complex networks [38].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have analysed network properties from different perspectives, depending on the type and complexity of networks. Entropy-based analysis has been used to identify influential nodes using local information dimensionality [37]. Fractal dimensions are being explored to determine the vulnerability of complex networks [38].…”
Section: Discussionmentioning
confidence: 99%
“…Studies on influencer nodes reveal that such individuals help in fast information diffusion across their social networks because they are highly connected individuals with a higher degree centrality in their network [40], [41]. In a recent research, T. Wen and Y. Deng [42] investigated six real world complex networks to identify the influencer nodes using Shannon entropy measure. They found that individuals are more influential when they have a higher centrality in local information dimensionality.…”
Section: ) Influencersmentioning
confidence: 99%
“…Among these, the most relevant study to our research problem is Identification of influencers in complex networks, i.e. [42]. But since [42] focuses on local information dimensionality, rather than turnover intention of influencer employees studied in this paper, it cannot be used for turnover studies of organizational networks.…”
Section: ) Influencersmentioning
confidence: 99%
“…Entropy plays an important role in wide range 66 . Shannon has first proposed Shannon entropy in information theory 67 .…”
Section: Entropy Of Bpasmentioning
confidence: 99%